Success Factors of Commercial Banks in Nepal (Pravaha, 2025)
The study aims to analyze the determinants of the financial performance of commercial banks in Nepal. A descriptive and causal research design is adopted in the study. The population consists of twenty commercial banks listed on NEPSE. HBL, NABIL, NIMB, SCNBL, EBL, and SANIMA were randomly selected, comprising ten years of data and sixty firm-years observations. Descriptive and inferential statistical analyses have been performed in the study. The study concludes that Nepalese commercial banks maintain an overly high capital adequacy ratio. Banks size is adequate when considering the overall asset base. However, commercial banks remain unable to fully employ all their available assets in various forms. The rising net interest margin ratio suggests that commercial banks are successfully mobilizing and utilizing their available assets. The financial performance of commercial banks is positively impacted by increase in gross domestic product. The capital adequacy ratio has a positive effect on financial performance. Nonetheless, bank size, measured by total assets, has a negative effect on financial performance.